Rehabilitation for ataxia study: protocol for a randomised controlled trial of an outpatient and supported home-based physiotherapy programme for people with hereditary cerebellar ataxia. Issue 12 (17th December 2020) - Milne, Sarah C; Corben, Louise A; Roberts, Melissa; Szmulewicz, David; Burns, J; Grobler, Anneke C; Williams, Shannon; Chua, Jillian; Liang, Christina; Lamont, Phillipa J; Grootendorst, Alison C; Massey, Libby; et al.
Abstract : Introduction: Emerging evidence indicates that rehabilitation can improve ataxia, mobility and independence in everyday activities in individuals with hereditary cerebellar ataxia. However, with the rarity of the genetic ataxias and known recruitment challenges in rehabilitation trials, most studies have been underpowered, non-randomised or non-controlled. This study will be the first, appropriately powered randomised controlled trial to examine the efficacy of an outpatient and home-based rehabilitation programme on improving motor function for individuals with hereditary cerebellar ataxia. Methods and analysis: This randomised, single-blind, parallel group trial will compare a 30-week rehabilitation programme to standard care in individuals with hereditary cerebellar ataxia. Eighty individuals with a hereditary cerebellar ataxia, aged 15 years and above, will be recruited. The rehabilitation programme will include 6 weeks of outpatient land and aquatic physiotherapy followed immediately by a 24- week home exercise programme supported with fortnightly physiotherapy sessions. Participants in the standard care group will be asked to continue their usual physical activity. The primary outcome will be the motor domain of the Functional Independence Measure. Secondary outcomes will measure the motor impairment related to ataxia, balance, quality of life and cost-effectiveness. Outcomes will be administered at baseline, 7 weeks, 18 weeks and 30 weeks by a physiotherapist blinded to group allocation. A repeated measures mixed-effects linear regression model will be used to analyse the effect of the treatment group for each of the dependent continuous variables. The primary efficacy analysis will follow the intention-to-treat principle. Ethics and dissemination: The study has been approved by the Monash Health Human Research Ethics Committee (HREC/18/MonH/418) and the Human Research Ethics Committee of the Northern Territory Department of Health and Menzies School of Health Research (2019/3503). Results will be published in peer-reviewed journals, presented at national and/or international conferences and disseminated to Australian ataxia support groups. Trial registration number: ACTRN12618000908235.